Eksplorasi Peran Pengembangan Sumber Daya Manusisa Berbasis Teknologi Informasi Pada Komunitas Maysarakat Di Organisasi Olah Raga Kebugaran Indonesia (ORKI) Kota Tangerang Selatan - Yakup Hermansyah; Mitri Nelsi; Irfan Rizka Akbar (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This Community Service Program aims to explore the role of information technology-based human resource development in the Indonesian Fitness Sports Organization community, known as ORKI, in South Tangerang City. The main problems faced by the partner organization include the suboptimal capacity of human resources in communication, leadership, teamwork, time management, discipline, activity documentation, and the use of information technology to support organizational management. The implementation methods of this program included counseling, mentoring, participatory discussions, practical training on the use of simple information technology tools, and activity evaluation. The materials delivered covered human resource development, digital literacy, organizational communication, collaborative leadership, teamwork, time management, and the use of information technology for data management, documentation, publication, and activity evaluation. The results of the program showed that participants gained a better understanding of the importance of information technology-based human resource development in strengthening community organizational governance. Participants also demonstrated enthusiasm in joining the activities, engaging in discussions, and understanding the use of simple technology to support ORKI activities. Through this program, ORKI is expected to become a more adaptive, well-organized, communicative, and relevant community sports organization in response to the needs of the digital era...